ANALISIS PELAKSANAAN FUNGSI PENGAWASAN INSPEKTORAT TERHADAP PENYELENGGARAAN PEMERINTAHAN PROVINSI PAPUA - Suparmi Suparmi (Universitas Cenderawasih, 2019)
This study aims to obtain a clear picture of the effects of supervision which consists of routine supervision, individual supervision, and monitoring of the administration of Papua Province.The type of data used is qualitative data and quantitative data. Primary and secondary data is the source of the data used. Data collection techniques used are field data and literature study data. The study was conducted using qualitative analysis techniques and quantitative analysis consisting of research instrument tests, standard assumption tests, and multiple regression analysis.The results showed that the routine supervision variable partially had a significant influence on the administration of the Papua Province. While the special supervision and partial monitoring variables do not have a significant effect on the administration of the Papua Province. Variables of routine supervision, individual supervision, and simultaneous monitoring have a significant influence on the administration of Papua Province.The routine supervision variable is the most dominant factor influencing the administration of Papua Province.